2005
DOI: 10.1111/j.1479-828x.2005.00351.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an early pregnancy problem service on patient care and Emergency Department presentations

Abstract: Following the introduction of the Early Pregnancy Problem Service, women presenting with first trimester pain or bleeding who did not require emergency hospital admission spent significantly less time in the Emergency Department.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 10 publications
0
19
0
Order By: Relevance
“…Despite widespread reports regarding the clinical and economic benefits of UK‐based EPAUs, knowledge about the EPAU concept was either absent or limited among 85% of all participants in the present study. Nonetheless, knowledge levels were substantially higher among certain subgroups: graduated obstetricians and/or gynecologists, Dutch‐speaking respondents, and participants aged 50 years or older.…”
Section: Discussionmentioning
confidence: 75%
“…Despite widespread reports regarding the clinical and economic benefits of UK‐based EPAUs, knowledge about the EPAU concept was either absent or limited among 85% of all participants in the present study. Nonetheless, knowledge levels were substantially higher among certain subgroups: graduated obstetricians and/or gynecologists, Dutch‐speaking respondents, and participants aged 50 years or older.…”
Section: Discussionmentioning
confidence: 75%
“…An Australian study found that following the Sustained value of early pregnancy assessment in management of early pregnancy complications -10-year retrospective establishment of an early pregnancy problem service clinic, there was a significant reduction in the median length of stay in the ER for women experiencing pain or bleeding in early pregnancy; however, there was a non-significant reduction in the proportion of assessments and reassessments in the ER. 19 Another study found that implementing the use of a gynaecology outpatient clinic decreased the proportion of ER assessments for miscarriages from 31% in 2001 to 17% in 2009. 20 Our study showed that throughout a 10-year period, the EPAC has continued to provide care to women with early pregnancy complications; however, there has not been an impact in reducing the number of ER assessments and reassessments for miscarriage and ectopic pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of health system factors that potentially impact on LOS in the ED for women with early pregnancy complications. Several studies have found that need for an ultrasound imaging can increase LOS and the establishment of an early pregnancy service can reduce it . There is some evidence that midwifery and nurse lead care can facilitate reduced inpatient stay for pregnant women, but only limited evidence supporting the role of specialist midwives in EDs for women with early pregnancy complications.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have found that need for an ultrasound imaging can increase LOS 16 and the establishment of an early pregnancy service can reduce it. 17 There is some evidence that midwifery and nurse lead care can facilitate reduced inpatient stay for pregnant women, [18][19][20] but only limited evidence supporting the role of specialist midwives in EDs for women with early pregnancy complications. We sought to investigate the impact patient review by the CMC had on the ED LOS for women presenting with early pregnancy complications and to identify other factors (such as time of presentation and triage category) that impact on LOS.…”
Section: Introductionmentioning
confidence: 99%